PROBLEMATIKA MOTIVASI BELAJAR PENDIDIKAN AGAMA ISLAM DI ERA DIGITAL: PENERAPAN MULTIMEDIA LURING SEBAGAI SOLUSI INSTRUKSIONAL DI PESANTREN - Ahmad Fahrizal Lathif; Zainuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology has changed the learning characteristics of Generation Z, who tend to be responsive to visual and interactive media. However, Islamic educational institutions based on Islamic boarding schools often face regulatory dilemmas in the form of restrictions on the use of personal devices, so that Islamic Religious Education (PAI) learning tends to return to conventional one-way methods that trigger student boredom. This study aims to explore the problem of declining motivation to learn PAI in grade X students at SMA An-Nur Hidayatullah Turen and examine the effectiveness of implementing offline multimedia as an instructional middle ground that adapts to pesantren regulations. This study uses a qualitative approach with a descriptive case study design. Data collection was carried out through direct observation, in-depth interviews with PAI teachers and grade X students, and documentation. Data analysis applies an interactive model that includes data reduction, data presentation, and conclusion drawing, with validity testing through triangulation of sources and techniques. The results show that the initial condition of PAI learning is dominated by the lecture method (teacher-centered) which triggers mental fatigue, drowsiness, and a decrease in students' intrinsic learning motivation due to overlapping material with pesantren studies. The implementation of offline multimedia in the form of visual presentations and videos of Islamic history using a laptop, LCD projector, and loudspeakers without internet access has been proven to increase student focus, enthusiasm, and active engagement in class.